Private Enforcement, Corruption, and Antitrust Design - Peter Grajzl; Andrzej Baniak (Center for Economic Studies and ifo Institute (CESifo), 2015)
Recent adoption of competition laws across the globe has highlighted the importance of institutional considerations for antitrust effectiveness and the need for comparative institutional analyses of antitrust that extend beyond matters of substantive law. Contributing to the resulting nascent research agenda, we examine how the rationale for enabling versus precluding private antitrust enforcement as one salient choice in antitrust design depends on whether antitrust enforcement is corruption-free or plagued by corruption. Contingent on the nature of adjudicatory bias, bribery either discourages private antitrust lawsuits or incentivizes firms to engage in frivolous litigation. Corruption expectedly reduces the effectiveness of antitrust enforcement at deterring antitrust violations. Yet private antitrust enforcement as a complement to public enforcement can be social welfare-enhancing even in the presence of corruption. Under some circumstances, corruption actually increases the relative social desirability of private antitrust enforcement. Our analysis highlights that the appropriate design of antitrust institutions is context-specific.
Keywords: K21; L40; H11; P51; 330; antitrust; corruption; private enforcement; public enforcement; institutional design